Thou shalt not fail? Using theological impulses to critique the heroic bias in transformational leadership theory - Fourie, Willem; Höhne, Florian (Leadership, 2019)
Leaders whose mistakes are made public are often under pressure to relinquish their positions. The expectation that true leaders should be infallible is particularly pronounced in transformational leadership theory. Its heroic bias seems to point towards a conception of leadership that is at odds with the inevitability of human failure. In this article, we use impulses from Protestant theology to identify and critique the heroic bias in transformational leadership theory. We use theory from beyond leadership scholarship and from beyond its conventional Anglophone locations, to show that fallibility does not necessarily disable leaders from contributing to transformational changes. We show that the acknowledgement of leaders’ fallibility has the potential to correct unrealistic and problematic views of leaders’ influence, correct utopian expectations of processes of change and empower followers.
CRIS-Team Scopus Importer:2023-04-11
Keywords: heroic bias; Jürgen Moltmann; leadership and religion; leadership theory and theology; Transformational leadership; transformational leadership criticism